2020
DOI: 10.1167/iovs.61.14.15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Atropine Treatment on Choroidal Thickness in Myopic Children

Abstract: Purpose To examine the changes in choroidal thickness (ChT) after 6 months of 1% or 0.01% atropine treatment and the independent factors associated with eye elongation. Methods A total of 207 myopic children aged 6 to 12 years were recruited and randomly assigned to groups A and B in a ratio of 1:1. Participants in group A received 1% atropine once a day for 1 week, and then once a week for 23 weeks. Participants in group B received 0.01% atropine once a day for 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 52 publications
1
39
0
Order By: Relevance
“…The thickening response of the choroid was rapid and significant within only 1 month or even 1 week of atropine treatment (1%, 0.3% and 0.01% atropine) and became slower and insignificant after that [61][62][63]. In the present study, the thickening of subfoveal ChT in the atropine group was 5.20 ± 10.86 lm at 1-month visit, which is comparable to the aforementioned study.…”
Section: Discussionsupporting
confidence: 87%
“…The thickening response of the choroid was rapid and significant within only 1 month or even 1 week of atropine treatment (1%, 0.3% and 0.01% atropine) and became slower and insignificant after that [61][62][63]. In the present study, the thickening of subfoveal ChT in the atropine group was 5.20 ± 10.86 lm at 1-month visit, which is comparable to the aforementioned study.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, an in vitro study on human cells proved that atropine was able to decrease in vitro ECM biosynthesis in the choroid, with local fibroblasts improving scleral blood perfusion through the choroid, improving ECM perfusion and thus decreasing myopia progression [ 81 ]. Furthermore, atropine has been able to increase choroidal thickness in both healthy and myopic children and to block choroidal thinning associated with hyperopic defocus [ 82 , 83 , 84 , 85 ]. Future research could provide us with an exhaustive theoretical model that would explain in detail the biological pathways and effectors that determine the observed efficacy of this drug.…”
Section: Resultsmentioning
confidence: 99%
“…A week of twice daily administration of 1% atropine ophthalmic gel led to a significant increase in subfoveal and parafoveal CT 18 . Two additional studies investigating the effect of 1% atropine have found similar findings of increased CT 19,20 . The study by Jiang et al .…”
Section: Resultsmentioning
confidence: 87%